[zu: Rolf Dieter Brinkmann:] Dieses Gedicht hat keinen Titel - Elit, Stefan (Rolf Dieter Brinkmann. Seine Lyrik in Einzelinterpretationen)

[zu: Rolf Dieter Brinkmann:] Oh, friedlicher Mittag - Elit, Stefan (Rolf Dieter Brinkmann. Seine Lyrik in Einzelinterpretationen)

[überarb. u. aktualis. Verfasserart.:] Wogatzki, Benito - Elit, Stefan (Killy. Literaturlexikon. Autoren und Werke des deutschsprachigen Kulturraums, 2., vollst. überarb. Aufl., Bd. 12)

Liebesgaben. Kommunikative, performative und poetologische Dimensionen in der Literatur des Mittelalters und der Frühen Neuzeit

„Inzest und Aufschub. Zur Erzähllogik im Apollonius von Tyrland“ - Egidi, Margreth (Liebesgaben. Kommunikative, performative und poetologische Dimensionen in der Literatur des Mittelalters und der Frühen Neuzeit (Philologische Studien und Quellen 240))

„Perspektiven einer Poetik der Liebesgabe. Einleitung“ - Egidi, Margreth; Wedell, Moritz (Liebesgaben. Kommunikative, performative und poetologische Dimensionen in der Literatur des Mittelalters und der Frühen Neuzeit (Philologische Studien und Quellen 240))

Prior entry and temporal attention: Cueing affects order errors in RSVP. - Hilkenmeier, Frederic; Olivers, Christian N. L.; Scharlau, Ingrid (Journal of Experimental Psychology: Human Perception and Performance)
The law of prior entry states that attended objects come to consciousness more quickly than unattended ones. This has been well established in spatial cueing paradigms, where two task-relevant stimuli are presented near-simultaneously at two different locations. Here, we suggest that prior entry also plays a pivotal role in temporal attention paradigms, where stimuli appear at the same location but at distinct moments in time, in rapid serial presentation (RSVP). Specifically, we hypothesize that prior entry can explain temporal order reversals in reporting two targets from RSVP. In support of this, three experiments show that cueing attention toward either of the targets has a strong influence on order errors. We conclude that prior entry provides a viable explanation of the way in which relevant information is prioritized in RSVP. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: attentional blink; attentional enhancement; lag-1 sparing; prior entry; temporal cueing; visual attention; rapid serial presentation; Adolescent; Adult; Attention; Attentional Blink; Color Perception; Cues; Female; Humans; Male; Neuropsychological Tests; Pattern Recognition; Visual; Time Factors; Visual Perception; Young Adult; Cues; Serial Recall; Visual Attention; Eyeblink Reflex

At the mercy of prior entry: Prior entry induced by invisible primes is not susceptible to current intentions. - Weiß, Katharina; Scharlau, Ingrid (Acta Psychologica)
If one of two events is attended to, it will be perceived earlier than a simultaneously occurring unattended event. Since 150 years, this effect has been ascribed to the facilitating influence of attention, also known as prior entry. Yet, the attentional origin of prior-entry effects¹ has been repeatedly doubted. One criticism is that prior-entry effects might be due to biased decision processes that would mimic a temporal advantage for attended stimuli. Although most obvious biases have already been excluded experimentally (e.g. judgment criteria, response compatibility) and prior-entry effects have shown to persist (Shore, Spence, & Klein, 2001), many other biases are conceivable, which makes it difficult to put the debate to an end. Thus, we approach this problem the other way around by asking whether prior-entry effects can be biased voluntarily. Observers were informed about prior entry and instructed to reduce it as far as possible. For this aim they received continuous feedback
Keywords: intentions; events; attention; decision processes; Adult; Attention; Choice Behavior; Cues; Female; Humans; Intention; Judgment; Male; Middle Aged; Reaction Time; Time Perception; Visual Perception; Attention; Decision Making; Experiences (Events); Intention

Spatial mislocalization as a consequence of sequential coding of stimuli. - Priess, Heinz-Werner; Scharlau, Ingrid; Becker, Stefanie I.; Ansorge, Ulrich (Attention, Perception, & Psychophysics)
In three experiments, we tested whether sequentially coding two visual stimuli can create a spatial misperception of a visual moving stimulus. In Experiment 1, we showed that a spatial misperception, the flash-lag effect, is accompanied by a similar temporal misperception of first perceiving the flash and only then a change of the moving stimulus, when in fact the two events were exactly simultaneous. In Experiment 2, we demonstrated that when the spatial misperception of a flash-lag effect is absent, the temporal misperception is also absent. In Experiment 3, we extended these findings and showed that if the stimulus conditions require coding first a flash and subsequently a nearby moving stimulus, a spatial flash-lag effect is found, with the position of the moving stimulus being misperceived as shifted in the direction of its motion, whereas this spatial misperception is reversed so that the moving stimulus is misperceived as shifted in a direction opposite to its motion when the c
Keywords: spatial mislocalization; sequential coding; stimulus parameters; Attention; Discrimination (Psychology); Humans; Judgment; Motion Perception; Optical Illusions; Orientation; Pattern Recognition; Visual; Psychophysics; Space Perception; Cognitive Processes; Motion Perception; Perceptual Localization; Spatial Perception; Stimulus Parameters; Consequence

The dynamics of prior entry in serial visual processing. - Hilkenmeier, Frederic; Scharlau, Ingrid; Weiß, Katharina; Olivers, Christian N. L. (Visual Cognition)
An attended stimulus reduces the perceptual latency of a later stimulus at the same location, leading to the intriguing finding that the perceived order between the two is often reversed. This prior-entry effect has been well established in a number of different cueing paradigms, mostly involving spatial attentional shifts. Here we assess the time-course of prior entry when all stimuli appear in rapid serial presentation at one location. Our findings indicate that the size of the attentional enhancement is strongly affected by the stimulus onset asynchrony between cue and target, with a rapid early peak, followed by decay. When task-irrelevant cues are used, the cueing effect on prior entry is short-lived and peaks as early as 50 ms. The benefit extends to about 100 ms when task-relevant cues are employed. These results fit with a straightforward computational model of transient attentional enhancement, peaking about 80 100 ms after stimulus detection. (PsycINFO Database Record (c) 20
Keywords: serial visual processing; prior entry dynamics; cueing paradigms; Cues; Visual Perception; Visual Search

Subjektive Theorien von Musikerinnen und Musikern zum Üben: Ein Beitrag an der Schnittstelle von Kognitionspsychologie - Bunte, Nicola; Scharlau, Ingrid (Popmusikforschung und Musikpädagogik)
This article reports on the findings of a qualitative interview study that investigated the individual ideas about practicing of nine musicians of different musical backgrounds, music genres, instruments, and learning biography. The findings reveal a variety of different aspects that are embedded in argumentative reasoning, and thus are analysed as subjective theories. According to differences in complexity with regards to content and argumentative structure we propose the following typification: 1) physical-technical constriction, 2) technique and interpretation centered type, and 3) creative-congnitive focus. A strict affiliation between these types and musical genre was not found.

Praxis nach Rezept? – Praxisbezug und Professionalität in den subjektiven Theorien von Lehramtsstudierenden - Schüssler, Renate; Keuffer, Josef; Günnewig, Kathrin; Scharlau, Ingrid (Schulpädagogik heute: Reform der Lehrerbildung in Deutschland, Österreich und der Schweiz)

Psychologie in der Lehrerbildung: Didaktische Konzeption zur Förderung von Conceptual Change, Selbstlern- und Reflexionskompetenz - Müsche, Hanna S.; Scharlau, Ingrid (Psychologiedidaktik und Evaluation IX)
Es wird eine psychologiedidaktische Konzeption skizziert, die vorwiegend auf der Basis empirischer Evidenz für das bildungswissenschaftliche Lehramtsstudium an der Universität Paderborn entwickelt wurde. Drei Bausteine greifen ineinander: Im Zentrum steht das problemorientierte Lernen, das durch beispielbasiertes Lernen und forschendes Lernen flankiert wird. Über die Einführung in psychologisches Wissen und Denken hinaus wird mit der Konzeption das Ziel verfolgt, die Studierenden in Conceptual Change-Prozessen, im selbstgesteuerten Lernen und in ihrer Reflexionsfähigkeit zu unterstützen und zu fördern. Insgesamt bewegt sich die Konzeption zwischen den lernpsychologischen Polen von Konstruktion und Instruktion und will sowohl einer Berufsfeldorientierung als auch einer Wissenschaftsorientierung Rechnung tragen.

Evaluierung medizinischer Volumenrendering-Algorithmen durch empirische Studien - Domik, Gitta; Arens, Stephan; Tünnermann, Jan; Scharlau, Ingrid (FIfF-Kommunikation)
Wie gut ist ein Rendering Algorithmus, der Bilder aus Daten generiert, die wiederum als Grundlage für eine medizinische Diagnose verwendet werden? In diesem Beitrag werden einerseits beispielhaft empirische Studien und ihre Ergebnisse vorgestellt, die solche Fragestellungen beantworten. Andererseits widmen wir uns auch der generellen Frage, welche Herausforderungen gemeistert werden müssen, um empirische Studien aufzustellen, die in Bezug auf korrekte medizinische Diagnosen und ihre zugrunde liegenden Rendering-Algorithmen sinnvoll sind.
Keywords: Informatik; Visualisierung; Psychologie; Experimentaldesign

Praxis nach Rezept? – Praxisbezug und Professionalität in den subjektiven Theorien von Lehramtsstudierenden - Schüssler, Renate; Keuffer, Josef; Günnewig, Kathrin; Scharlau, Ingrid (Reform der Lehrerbildung in Deutschland, Österreich und der Schweiz. Teil I: Analyse, Perspektiven und Forschung)

Reducing the flammability of ultra-high-molecular-weight polyethylene by triphenyl phosphate additives - Gonchikzhapov, M. B.; Paletsky, A. A.; Kuibida, L. V.; Shundrina, I. K.; Korobeinichev, O. P. (Combustion, Explosion, and Shock Waves)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Reduction of flammability of ultrahigh-molecular-weight polyethylene by using triphenyl phosphate additives - Korobeinichev, O.P.; Paletsky, A.A.; Kuibida, L.V.; Gonchikzhapov, M.B.; Shundrina, I.K. (Proceedings of the Combustion Institute)
Keywords: Physical and Theoretical Chemistry; Mechanical Engineering; General Chemical Engineering

Effektivität lexikalischer Strategietherapie im Vorschulalter. Eine randomisierte und kontrollierte Interventionsstudie - Ulrich, Tanja

Soziale Kognitionen, Sozialverhalten und Akzeptanz durch Gleichaltrige bei Kindern im Vorschulalter - Seifermann, Elke; Buhl, Heike M. (Diskurs Kindheits- und Jugendforschung)
Im vorliegenden Beitrag wird der Zusammenhang zwischen der sozialkognitiven Entwicklung und sozialer Akzeptanz durch Gleichaltrige im Vorschulalter dargestellt. Neben einem direkten Effekt sozialer Kognitionen auf die soziale Akzeptanz wird ein Mediationseffekt des Sozialverhaltens auf diesen Zusammenhang geprüft. Untersucht wurden 35 Kindergartenkinder im Alter von vier bis sechs Jahren. Zur Erfassung des sozialkognitiven Entwicklungsstandes bearbeiteten die Kinder Theory of Mindund Perspektivenübernahme-Aufgaben; ihre soziale Akzeptanz wurde durch Peernominationen sowie eine Erzieher-Beurteilung der Integration der Kinder in die Gruppe erhoben. Das prosoziale und aggressive Sozialverhalten der Kinder wurde durch die Erzieherinnen eingeschätzt. Es zeigte sich ein direkter Zusammenhang zwischen dem sozial-kognitiven Entwicklungsstand und der sozialen Akzeptanz der Kinder. Die Annahme, dass dieser Zusammenhang durch das prosoziale bzw. aggressive Verhalten der Kinder mediiert wird, bestätigte sich nur bedingt.
Keywords: sozial-kognitive Entwicklung; Sozialverhalten; soziale Akzeptanz; Vorschulalter

Perspektiven übernehmen. Textverstehen verbessern - Buhl, Heike M. (Literarisches Lernen im Anfangsunterricht. Theoretische Reflexionen, empirische Befunde, unterrichtspraktische Entwürfe)

Alkaline Salts to Counteract Bone Resorption and Protein Wasting Induced by High Salt Intake: Results of a Randomized Controlled Trial - Bühlmeier, Judith; Frings-Meuthen, Petra; Remer, Thomas; Maser-Gluth, Christiane; Stehle, Peter; Biolo, Gianni; Heer, Martina (The Journal of Clinical Endocrinology & Metabolism)
Keywords: Biochemistry (medical); Clinical Biochemistry; Endocrinology; Biochemistry; Endocrinology; Diabetes and Metabolism

Figurationen der Krise: Literarische Feuilletons der 20er und frühen 30er Jahre. Forschungsbericht - Öhlschläger, Claudia; Kernmayer, Hildegard (Zeitschrift für Germanistik, Neue Folge, XXII, H. 3/2012)

Das punctum der Moderne. Fotobücher und feuilletonistische Städtebilder der 1920er und frühen 1930er Jahre - Öhlschläger, Claudia; Kernmayer, Hildegard (Zeitschrift für Germanistik Heft 3/2012)

Lexikalische Strategietherapie für Vorschulkinder mit dem Wortschatzsammler - Ulrich, Tanja; Schneggenburger, K (Sprachförderung und Sprachtherapie in Schule und Praxis)

Effects of the Strategy Therapy "Lexicon Pirate" on Lexical Deficits in Preschool age: a Randomized Controlled Trial. - Motsch, H.J; Ulrich, Tanja (Child Language Teaching and Therapy)

„Wortschatzsammler und Wortschatzfinder“- Effektivität neuerTherapieformate bei lexikalischen Störungen im Vorschulalter - Motsch, H.J; Ulrich, T (Die Sprachheilarbeit)

Geschichte und Präsenz. Überlegungen zum gegenwärtigen ‚Ort‘ historischen Erzählens am Beispiel von Javier Cercas’ Anatomie eines Augenblicks - Schlieper, Hendrik (Literatur und Theorie seit der Postmoderneu)

The Female Threshold. On Paratext and Gender in Lafayette’s La Princesse de Montpensier - Schlieper, Hendrik; Steinbrügge, Lieselotte (Papers on French Seventeenth Century Literature 76)

Diskrepante Väterfiguren: Haus, Familie und Liebe in Molières „École des femmes“ - Steigerwald, Jörn (Romanistische Zeitschrift für Literaturgeschichte)

Realismus nach den europäischen Avantgarden. Ästhetik, Poetologie und Kognition in Literatur und Film der Nachkriegszeit

Suchbewegungen im Raum des Humanitären. Topographien der Bewohnbarkeit im Nachkriegsrealismus von Heinrich Böll und Vasco Pratolini - Öhlschläger, Claudia; Römhild, Friederike (Realismus nach den europäischen Avantgarden. Ästhetik, Poetologie und Kognition in Literatur und Film der Nachkriegszeit)

Chronik eines Verlusts. Rekonfigurationen der Heiligen Familie in Michelangelo Antonionis ́Il Grido ́ (1957) - Öhlschläger, Claudia (Antonioni revisited)

Abstraktion im Licht der Faszination. Wilhelm Worringer am Ort des Primitivismus - Öhlschläger, Claudia (Literarischer Primitivismus)

Wiederabdruck von: "Medialität und Poetik des trompe l ́œil. W.G. Sebald und Jan Peter Tripp“ - Öhlschläger, Claudia (W.G. Sebald. Neue Wege der Forschung)

„Meraviglioso Adone“: Das Wunderbare als Lizenz episch-didaktischer Dichtung bei Giovan Battista Marino - Steigerwald, Jörn (Valeska Erosionen der Rhetorik? Ambiguitäts- und Umsemantisierungsstrategien in den Künsten der Frühen Neuzeit)

La galanterie des dieux antiques: Chapelain critique de l’“Adone“ du cavalier Marin - Steigerwald, Jörn (Littératures classiques 77)

Affekt-Erzählungen: Die galanten Novellen Scudérys und Villedieus - Steigerwald, Jörn (Galanterie als Verhaltenskonzept in der Literatur der Frühen Neuzeit)

Schöne neue Menschen: Michel Houellebecqs „Les particules élémentaires“ - Steigerwald, Jörn (Menschen machen. Die hellen und die dunklen Seiten humanwissenschaftlicher Optimierungsprogramme)

Die Grenzen der Höflichkeit : Molières „Le Misanthrope“ - Steigerwald, Jörn (Rhetorik. Ein internationales Jahrbuch)

Positionierung. Zur Entwicklung des Gebrauchs modalisierender Prozeduren in argumentativen Texten von Schülern und Studenten - Rezat, Sara; Gätje, Olaf; Steinhoff, Torsten (Textroutinen. Theorie, Erwerb und didaktisch-mediale Modellierung)

Mittendrin statt nur dabei: Inklusion in Krippe und Kindergarten - Albers, Timm

Zuwanderungsgeschichte(n) – Überlegungen zur Relevanz biografischen, interkulturellen Schreibens im Deutschunterricht - Zierau, Cornelia (Alman Dili ve Edebiyatı Dergisi. Studien zur deutschen Sprache und Literatur XXVII 1/2012)

Mehrsprachigkeit als Thema des Literaturunterrichts. Erzählungen von Emine Sevgi Özdamar und Yoko Tawada - Zierau, Cornelia (Literatur im Unterricht: Texte der Gegenwartsliteratur für die Schule (LiU) 13/2012: Heft 3)

Extending UML for Electronic Systems Design: A Code Generation Perspective - Vanderperren, Yves; Müller, Wolfgang; He, Da; Mischkalla, Fabian; Dahaene, Wim (Design Technology for Heterogeneous Embedded Systems)
The Unified Modeling Language (UML) is now widely accepted by the software community. More recently, UML has attracted attention as a unification language for systems description combining both hardware and software components. First, it has been recognized that electronic systems design can no longer be seen as an isolated hardware design activity. In addition, recent advances in tools supporting high level hardware synthesis from electronic system level languages, which are predominantly based on C/C++, open new perspectives for automatic code generation from UML models and opportunities to enhance the link between a high level specification and a concrete hardware/software implementation. Finally, UML has become a general purpose language which can be customized for specific purposes, such as the modelization of electronic systems. This chapter presents recent advances of the UML language applied to System-on-Chip (SoC) and hardware-related embedded systems design. In particular, several examples of specific UML customizations (UML profiles) relevant for SoC design are summarized. Various approaches associating UML with existing hardware/software design languages are presented. The question of tool support and association with well-known simulation environments, such as MATLAB/Simulink, is addressed as well. A concrete example of a UML profile for hardware/software co-modeling and code generation for hardware/software co-simulation is presented in more details for illustration purposes.

Die Geschichte meiner ‚Stoffe’. Literarische Umsetzung Erkenntnistheoretischer Fragen in Friedrich Dürrenmatts autobiographischem Projekt 'Stoffe I-IX' - Famula, Marta (Vielheit und Einheit der Germanistik weltweit (= Publikationen der Internationalen Vereinigung für Germanistik 8))

Förderschwerpunkt Lernen – wohin? - Rauh, B; Laubenstein, Désirée; Anken, L.; Auer, H.-L.

Simulation and Experimental Analysis of Mixed Lubrication of K Type Worm Gear Drives - Magyar, Balázs; Sauer, B; Horák, P

Kontaktmodellierung von technisch rauen Oberflächen - Magyar, Balázs; Sauer, B

Eine Schule für alle oder eine Schule für jeden – Gedankenfragmente zu diskursiven Praktiken im Rahmen aktueller Inklusionsdiskussionen - Laubenstein, Désirée (Sonderpädagogik und Inklusion)

Genderforschung im Feld der beruflichen Orientierung und Qualifikation von Menschen mit Benachteiligungen/Behinderungen - Laubenstein, Désirée; Heger, M. (In: Heilpädagogische Forschung, Band 38, Heft 2)

Dran bleiben. Benachteiligungen von jungen Frauen im beruflichen System finden immer noch zu wenig Beachtung - Heger, M.; Laubenstein, Désirée (In: Impulse, Nr. 60)

Tribological Investigation of K Type Worm Gear Drives - Magyar, Balázs; Sauer, B; Horák, P (Acta Polytechnica Hungarica)

Tribo-dynamische Untersuchungen von Zylinderschneckengetrieben - Magyar, Balázs

Academic procrastination: The perspective of university counsellors - Patrzek, Justine; Grunschel, Carola; Fries, Stefan (International Journal for the Advancement of Counselling)

Transient and Steady-State Shear Banding in a Lamellar Phase as Studied by Rheo-NMR - Medronho, Bruno; Olsson, Ulf; Schmidt, Claudia; Galvosas, Petrik (Zeitschrift für Physikalische Chemie)
Abstract Flow fields and shear-induced structures in the lamellar (L α ) phase of the system triethylene glycol mono n -decyl ether (C 10 E 3 )/water were investigated by NMR velocimetry, diffusometry, and 2 H NMR spectroscopy. The transformation from multilamellar vesicles (MLVs) to aligned planar lamellae is accompanied by a transient gradient shear banding. A high-shear-rate band of aligned lamellae forms next to the moving inner wall of the cylindrical Couette shear cell while a low-shear-rate band of the initial MLV structure remains close to the outer stationary wall. The band of layers grows at the expense of the band of MLVs until the transformation is completed. This process scales with the applied strain. Wall slip is a characteristic of the MLV state, while aligned layers show no deviation from Newtonian flow. The homogeneous nature of the opposite transformation from well aligned layers to MLVs via an intermediate structure resembling undulated multilamellar cylinders is confirmed. The strain dependence of this transformation appears to be independent of temperature. The shear diagram, which represents the shear-induced structures as a function of temperature and shear rate, contains a transition region between stable layers and stable MLVs. The steady-state structures in the transition region show a continuous change from layer-like at high temperature to MLV-like at lower temperature. These structures are homogeneous on a length scale above a few micrometers.
Keywords: Physical and Theoretical Chemistry

Novel Self-Assembled Nanoparticles of Testosterone-Modified Glycol Chitosan and Fructose Chitosan for Controlled Release - Quiñones, Javier Pérez; Gothelf, Kurt V.; Kjems, Jørgen; Heras, Angeles; Schmidt, Claudia; Peniche, Carlos (Journal of Biomaterials and Tissue Engineering)
Keywords: Biomedical Engineering; Medicine (miscellaneous); Bioengineering; Biotechnology

Embedding DNA in surfactant mesophases: The phase diagram of the ternary system dodecyltrimethylammonium–DNA/monoolein/water in comparison to the DNA-free analogue - Bilalov, Azat; Elsing, Jonas; Haas, Eva; Schmidt, Claudia; Olsson, Ulf (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Structural Evolution in the Isotropic Channel of a Water–Nonionic Surfactant System That Has a Disconnected Lamellar Phase: A 1H NMR Self-Diffusion Study - Stubenrauch, Cosima; Kleinschmidt, Felix; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

N,O6-partially acetylated chitosan nanoparticles hydrophobically-modified for controlled release of steroids and vitamin E - Quiñones, Javier Pérez; Gothelf, Kurt Vesterager; Kjems, Jørgen; Caballero, Ángeles María Heras; Schmidt, Claudia; Covas, Carlos Peniche (Carbohydrate Polymers)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Self-assembled nanoparticles of glycol chitosan – Ergocalciferol succinate conjugate, for controlled release - Quiñones, Javier Pérez; Gothelf, Kurt Vesterager; Kjems, Jørgen; Caballero, Ángeles María Heras; Schmidt, Claudia; Covas, Carlos Peniche (Carbohydrate Polymers)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Self-assembled nanoparticles of modified-chitosan conjugates for the sustained release of dl-α-tocopherol - Quiñones, Javier Pérez; Gothelf, Kurt Vesterager; Kjems, Jørgen; Yang, Chuanxu; Caballero, Angeles María Heras; Schmidt, Claudia; Covas, Carlos Peniche (Carbohydrate Polymers)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

"Borussia", "Pfeffer", "Explosion" – Latinismen auf der Spur - Tophinke, Doris (Praxis Deutsch)

Streitgeschichten – ein Buchprojekt - Tophinke, Doris (Praxis Deutsch)

Andersschreiben als Gegenstand der linguistischen Forschung - Schuster, Britt-Marie; Tophinke, Doris (Andersschreiben. Formen, Funktionen, Traditionen)

Schreiben 2.0. Schriftlinguistische Beobachtungen und schriftdidaktische Perspektiven - Tophinke, Doris (Germanistische Mitteilungen. Zeitschrift für Deutsche Sprache, Literatur und Kultur)

Syntaktischer Ausbau im Mittelniederdeutschen. Theoretisch-methodische Überlegungen und kursorische Analysen - Tophinke, Doris (Niederdeutsches Wort)

Wild Style. Graffiti-Writing zwischen Schrift und Bild - Papenbrock, Martin; Tophinke, Doris (Andersschreiben. Formen, Funktionen, Traditionen)

“Seit ein Gespräch wir sind und hören voneinander” – eine Einführung - Rauh, B.; Laubenstein, Désirée; Anken, L.; Auer, H.-L. (Förderschwerpunkt Lernen – wohin?)

Für welches Ziel und zu welchem Zweck braucht man heute noch einen Förderschwerpunkt Lernen? - Rauh, B.; Laubenstein, Désirée; Auer, H.-L. (Förderschwerpunkt Lernen – wohin?)

Konstruktionen der Akteure im Förderschwerpunkt Lernen über Gegenwart und Zukunft ihres Gegenstandes – Ergebnisse der qualitativen Analyse von Expertendiskussionen. - Laubenstein, Désirée; Rauh, B. (Förderschwerpunkt Lernen – wohin?)

Credit risk securitization and bank soundness: Evidence from the microlevel for Europe - Michalak, Tobias C.; Uhde, André (Quarterly Review of Economics and Finance)
Using a unique sample of 749 cash and synthetic securitization transactions issued by 60 stock-listed bank holdings in the EU-13 plus Switzerland over the period from 1997 to 2007 this paper provides empirical evidence that credit risk securitization has a negative impact on the issuing banks’ financial soundness. Baseline findings hold even when controlling for likely reverse causality by employing instrumental variable techniques and substituting the accounting-based z-score ratio by market-based indicators of bank risk. Moreover, investigating the relationship between credit risk securitization and single z-score components in order to evaluate significant transmission channels proposed by relevant theoretical literature, we find a negative impact of securitization on bank profitability and capital environment as well as a positive relationship between securitization and the issuing bank's return volatility. Against the background of our empirical results we underline that the decision by the Basel Committee to enhance the new Basel III framework in the field of securitization is a step in the right direction.
Keywords: Credit risk securitization Bank soundness European banking

Cross-border bank lending - Empirical evidence on further determinants from OECD banking markets - Müller, Oliver; Uhde, André (Journal of International Financial Markets, Institutions & Money)
Employing data on foreign bank claims from 13 OECD countries on 51 emerging markets between 1993 and 2007, this study investigates specific characteristics of OECD banking markets and lending banks as new important determinants of cross-border lending. We initially provide empirical evidence that in addition to well-accepted “gravity measures”, characteristics of OECD banking markets as well as lending banks’ attributes may describe further important determinants of cross-border bank lending with regard to our sample. Building subsamples of more-developed emerging markets vs. frontier markets, addressing (non) common lender relationships and analyzing cross border lending flows during different time periods, our analysis additionally reveals that both the determinants’ explanatory power and their direction of impact notably vary with respective subsamples.
Keywords: Foreign bank claims; Gravity measures; OECD banking markets’ characteristics; Lending banks’ characteristics

Wealth effects of credit risk securitization in European Banking - Farruggio, Christian; Michalak, Tobias C.; Uhde, André (Journal of Business Finance and Accounting)
Using a unique cross‐sectional dataset of 381 cash and synthetic securitizations issued by 53 banks from the EU‐15 plus Switzerland between 1997 and 2007, this paper provides empirical evidence for time‐dependent negative wealth effects of credit risk securitization announcements in European banking. Baseline results hold when comparing estimated wealth effects with a control group of similar but non‐securitizing banks for the relevant time period. Moreover, building several sub samples we find that the nexus between credit risk securitization, the issuing banks’ overall risk exposure and wealth effects is associated with a variety of transaction‐ and bank‐specific factors.
Keywords: wealth effects; credit risk securitization; Europe; event study

Measuring the quality of banking supervision revisited - Assessments by German banks before and during the financial crisis - Paul, Stephan; Stein, Stefan; Uhde, André (Journal of Governance and Regulation)
This contribution presents and discusses main results of a new survey on the assessment of supervisory quality among German banks in 2010. In particular, it is analyzed if and how supervised banks’ perception of the quality of supervisory authorities and their instruments has changed due to the financial crisis starting in mid-2007. Subsequently, results from the recent survey are compared with findings provided by a former study carried out by the authors in 2006 (Paul, Stein and Uhde, 2008).
Keywords: banking supervision; quality; assessment; banking sector

All-optical tunability of microdisk lasers via photo-adressable polyelectrolyte functionalization - Piegdon, K. A.; Lexow, M.; Grundmeier, G.; Kitzerow, Heinz-Siegfried; Pärschke, K.; Mergel, D.; Reuter, Dirk; Wieck, A. D.; Meier, Cedrik (Optics Express)

All-optical tunability of microdisk lasers via photo-adressable polyelectrolyte functionalization - Piegdon, K. A.; Lexow, M.; Grundmeier, G.; Kitzerow, Heinz-Siegfried; Pärschke, K.; Mergel, D.; Reuter, Dirk; Wieck, A. D.; Meier, C. (Optics Express)

Sovereign Risk and Bank-Specific CDS Pricing - Meine, Christian; Michalak, Tobias C.; Uhde, André
Employing time series of single-name CDS market spreads from 29 European banks located in the EU-12 plus Switzerland and the UK over the period from January 2004 through September 2010 this paper analyses the relationship between increasing sovereign risk and bank-specific CDS pricing. Results from calculating relative CDS spread deviations (model minus market spreads) initially reveal a price bubble in the European CDS market until the beginning of the financial crisis in mid-2007. From this point in time the gap narrows remarkably during the financial crisis and sovereign debt crisis period. Corresponding to these findings, the empirical analysis reveals a negative impact of sovereign risk on calculated CDS spread differentials indicating a spill-over effect between sovereign risk and bank risk and hence, a positive effect on bank-specific CDS pricing. Further analyses reveal that the perception of sovereign risk is not crisis- but country-dependent suggesting that bank-specific CDS market spreads may already include a premium to cover sovereign risk from PIIGS countries during the pre-crisis period in Europe.
Keywords: Sovereign risk; Structural credit risk models; bank-specific CDS pricing

Kultur und Politik am Hof der Herzöge von Burgund - Kamp, Hermann (Europa im 15. Jahrhundert. Herbst des Mittelalters - Frühling der Neuzeit)

Wertorientierte Vergütung des Aufsichtsrats - Auswirkungen auf den Unternehmenswert - Ebert, Michael; Zein, Nicole (Betriebswirtschaftliche Forschung und Praxis)

Neue Episteme: Die biokybernetische Konfiguration der Technowissenschaftskultur - Weber, Jutta (Handbuch Wissenschaftssoziologie)

Den Dualismus überlisten: Negative Dialektik, Cat’s Cradle und die Idee unverstellter Erkenntnis - Weber, Jutta (Dualitäten)

An Approach for Self-Reconfiguring and Fault-Tolerant Distributed Real-Time Systems - Klobedanz, Kay; Müller, Wolfgang; Rettberg, Achim
In this paper we present an approach for the self reconfiguration of distributed micro-controllers for increased fault tolerance. Based on a modified distributed system topology utilizing a time division multiple access (TDMA) protocol, i.e., Flex Ray, we present a self-organized distributed coordinator concept which performs the self-reconfiguration in the case of node failures. We introduce a distributed coordinator, which utilizes redundant slots in the Flex Ray communication schedule and combines messages in configured protocol frames and slots to avoid a complete bus restart. As such, the self-reconfiguration is realized by means of predetermined information about resulting changes in the communication dependencies and (re-)assignments determined in the design phase. To retrieve the necessary information, we present an analytical approach, which determines a combined solution for the initial configuration and all possible reconfigurations for the remaining nodes of the Flex Ray network in case of node failures. Hence, through this method we can design self-reconfiguring network-based systems enabling the handling of node failures for an increased fault tolerance.
Keywords: Real time systems; Fault tolerant systems; Schedules; Protocols; Redundancy; Delay

Towards an Enhanced UVM for SystemC - Oliveira, M. F.; Kuznik, Christoph; Müller, Wolfgang; Esen, V.; Ecker, W. (Proceedings of the Design & Verification Conference (DVCon))

Mutation-Analysis Driven Functional Verification of a Soft Microprocessor - Xie, Tao; Müller, Wolfgang; Letombe, Florian (Proceedings of SOCC2012)
This paper proposes a quality driven, simulation based approach to functional design verification, which applies mainly to IP-level HDL designs with well specified test instruction format and is evaluated on a soft microprocessor core MB-LITE [5]. The approach utilizes mutation analysis as the quality metric to steer an automated simulation data generation process. It leads to a simulation flow with two phases towards an enhanced mutation analysis result. First in a random simulation phase, an in-loop heuristics is deployed and adjusts dynamically the test probability distribution so as to improve the coverage efficiency. Next, for each remaining hard-to-kill mutant, a search heuristics on test input space is developed to iteratively locate a target test, using a specific objective cost function for the goal of killing HDL mutant. The effectiveness of this integrated two-phase simulation flow is demonstrated by the results with the MB-LITE microprocessor IP.
Keywords: Analytical models; Hardware design languages; Microprocessors; Cost function; Data models; Search problems; IP networks

An IP-XACT-TO-SystemC Model Generator for Mutation Analysis - Xie, Tao; Müller, Wolfgang (Proceedings of the MeCoES’12)

Schauspielmusik - Tumat, Antje (Wagner-Handbuch)

Uneingeleitete Nebensätze mit konditionaler Semantik im Mittelniederdeutschen - Wallmeier, Nadine (Niederdeutsche Syntax)

Teaching Experience - improving teacher education with experiential learning - Behr, Teresa; Temmen, Katrin (International Journal on New Trends in Education & their Implications (IJONTE))

When ideas circulate. A walk across disciplines and different uses of the ‘capability approach’ - Dahmen, Stephan; Bussi, Margherita (Transfer: European Review of Labour and Research)

Gender & Art: Selbstbilder und Selbstkonzepte in den Künsten (GENDER. Zeitschrift für Geschlecht, Kultur und Gesellschaft)
Die Vorstellung der künstlerischen Schöpfungskraft als ‚männliche Gabe‘ tradiert sich seit Jahrhunderten und nimmt Einfluss auf das Schaffen von Künstlerinnen und Künstlern. Die feministische Kunst offenbart diese Normierung und bietet dadurch Ansätze zur Auseinandersetzung mit dem (Selbst-)Verständnis von Kunst und Kunstschaffenden vor dem Hintergrund des anhaltenden Diskurses über Geschlecht. Die Beiträge in diesem Heft zeigen Beispiele einer solchen Herangehensweisen aus unterschiedlichen künstlerischen Genres.

Quasilimiting behavior for one-dimensional diffusions with killing - Kolb, Martin; Steinsaltz, David (Annals of Probability)
This paper extends and clarifies results of Steinsaltz and Evans [Trans. Amer. Math. Soc. 359 (2007) 1285–1234], which found conditions for convergence of a killed one-dimensional diffusion conditioned on survival, to a quasistationary distribution whose density is given by the principal eigenfunction of the generator. Under the assumption that the limit of the killing at infinity differs from the principal eigenvalue we prove that convergence to quasistationarity occurs if and only if the principal eigenfunction is integrable. When the killing at ∞ is larger than the principal eigenvalue, then the eigenfunction is always integrable. When the killing at ∞ is smaller, the eigenfunction is integrable only when the unkilled process is recurrent; otherwise, the process conditioned on survival converges to 0 density on any bounded interval.

Neue Episteme: Die biokybernetische Konfiguration der Technowissenschaftskultur - Weber, Jutta (Handbuch Wissenschaftssoziologie)

Mobility in Literature and Culture, 1500-1900

Fabrication of ZrO2 and ZrN Films by Metalorganic Chemical Vapor Deposition Employing New Zr Precursors - Banerjee, Manish; Srinivasan, Nagendra Babu; Zhu, Huaizhi; Kim, Sun Ja; Xu, Ke; Winter, Manuela; Becker, Hans-Werner; Rogalla, Detlef; de los Arcos de Pedro, Maria Teresa; Bekermann, Daniela; Barreca, Davide; Fischer, Roland A.; et al. (Crystal Growth & Design)

Sc2O3, Er2O3, and Y2O3 thin films by MOCVD from volatile guanidinate class of rare-earth precursors - Milanov, Andrian P.; Xu, Ke; Cwik, Stefan; Parala, Harish; de los Arcos de Pedro, Maria Teresa; Becker, Hans-Werner; Rogalla, Detlef; Cross, Richard; Paul, Shashi; Devi, Anjana (Dalton Transactions)

The Role of Oxygen and Surface Reactions in the Deposition of Silicon Oxide like Films from HMDSO at Atmospheric Pressure - Reuter, Rüdiger; Rügner, Katja; Ellerweg, Dirk; de los Arcos de Pedro, Maria Teresa; von Keudell, Achim; Benedikt, Jan (Plasma Processes and Polymers)

High power impulse magnetron sputtering discharges: Instabilities and plasma self-organization - Ehiasarian, A. P.; Hecimovic, A.; de los Arcos de Pedro, Maria Teresa; New, R.; Schulz-von der Gathen, V.; Böke, M.; Winter, J. (Applied Physics Letters)

Nanocomposites of carbon nanotubes embedded in a (Ti,Al)N coated film - Marot, L.; de los Arcos de Pedro, Maria Teresa; Bünzli, A.M.; Wäckerlin, C.; Steiner, R.; Oelhafen, P.; Meyer, E.; Mathys, D.; Spätig, P.; Covarel, G. (Surface and Coatings Technology)

Embedded argon as a tool for sampling local structure in thin plasma deposited aluminum oxide films - Prenzel, Marina; de los Arcos de Pedro, Maria Teresa; Kortmann, Annika; Winter, Jörg; von Keudell, Achim (Journal of Applied Physics)

Temporal evolution of the radial plasma emissivity profile in HIPIMS plasma discharges - Hecimovic, A; de los Arcos de Pedro, Maria Teresa; Schulz-von der Gathen, V; Böke, M; Winter, J (Plasma Sources Science and Technology)